Simulation of electronic properties of a quantum dot in transistor geometry at varying temperatures - Ahsan, Md. Galib (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Science in Physics, 2016